Archaeal community from the Northern Hangzhou Bay to the East China Sea: biogeography, ecological processes, and functional potential - Tian, Cunzhang; He, Xinping; Zhou, Hongwei; Liu, Cheng; Gao, Dengzhou; Chang, Yongkai; Zhao, Shanshan; Zhang, Wensong; Zhang, Zongxiao (Frontiers in Marine Science, 2024)
The archaeal communities in marine water significantly influence ecological health and stability. However, there are still gaps in our knowledge about the microbial ecological and functional characteristics of these groups. In this study, high-throughput sequencing dataset based on the 16S rRNA gene was analyzed to characterize and compare the biogeographic patterns of archaea in the coastal environment (the northern Hangzhou Bay). The results showed that Woesearchaeota, Thaumarchaeota, Euryarchaeota, and Crenarchaeota were the predominant phyla. The structure of archaea in the sediment exhibited a geographical pattern along the salinity gradient, which was significantly influenced by environmental gradients such as salinity, ammonium, total phosphorus content, pH, and total nitrogen content. Based on network analysis, the microbial community displayed a nonrandom co-occurrence pattern, and the microbial co-occurrence associations showed clear changes along the salinity gradient. Additionally, this study directly proved the existence of dispersal restriction in this strongly connected marine ecological system through null model analyses. Within this geographical range, we demonstrated that the variation in the archaeal community was not only due to the evident effect of environmental constraints (determinism) but also due to stochastic processes resulting from dispersal limitation. Furthermore, our results revealed that the key biogeochemical functions of the archaeal community also exhibited a clear salinity gradient, although the functional similarity did not change significantly along the salinity gradient. Moreover, the functional differences appear to be influenced by salinity, and the critical roles of archaeal diversity were highlighted. All these findings contribute to a deeper understanding of microbial ecology and key element transformation in this estuarine environment.